2020
DOI: 10.3390/biomimetics5020018
|View full text |Cite
|
Sign up to set email alerts
|

Biomimicry for Regenerative Built Environments: Mapping Design Strategies for Producing Ecosystem Services

Abstract: Built environment professionals must solve urgent and complex problems related to mitigating and adapting to climate change and biodiversity loss. Cities require redesign and retrofit so they can become complex systems that create rather than diminish ecological and societal health. One way to do this is to strategically design buildings and cities to generate and provide ecosystem services. This is an aspect of biomimicry, where whole ecosystems and their functions are emulated, in order to positively shift t… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
32
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(36 citation statements)
references
References 53 publications
0
32
0
1
Order By: Relevance
“…Much research has reported on the link between green and blue infrastructure, ecosystems health and ecosystem services (De Vries et al, 2016;Elmqvist et al, 2013;Grellier et al, 2017;Pedersen Zari and Hecht, 2020;Rapport, Costanza and McMichael, 1998). Research finds that opportunity lies in re-instating habitats and species that benefit urban biodiversity as well as contributing to human wellbeing (Tilman, Isbell and Cowles, 2014).…”
Section: Green and Blue Infrastructure And The Importance Of Ecosystementioning
confidence: 99%
See 1 more Smart Citation
“…Much research has reported on the link between green and blue infrastructure, ecosystems health and ecosystem services (De Vries et al, 2016;Elmqvist et al, 2013;Grellier et al, 2017;Pedersen Zari and Hecht, 2020;Rapport, Costanza and McMichael, 1998). Research finds that opportunity lies in re-instating habitats and species that benefit urban biodiversity as well as contributing to human wellbeing (Tilman, Isbell and Cowles, 2014).…”
Section: Green and Blue Infrastructure And The Importance Of Ecosystementioning
confidence: 99%
“…In this way, urban restoration through green and blue infrastructure solutions contributes to ecological, social, and cultural health in various holistic and interconnected ways (Hes and du Plessis, 2014;Mang and Reed, 2012;Pedersen Zari and Hecht, 2020). It does this by safeguarding the ecological and biological aspects of our unique native flora and fauna, while still filling our urban landscapes with life and meaningful experiences.…”
Section: Figure 3 Early Design Iteration Bruno Marques Jacqueline MCmentioning
confidence: 99%
“…Moving forward, it may be that the biomimicry field and associated networks develop unique pathways to explore each of these three opportunity types. For example, opportunities with potential for immediate implementation may be consolidated into a centralised database as suggested (leveraging, for example, the work undertaken by the Biomimicry Institute with 'Ask Nature' [29])-work that has now been initiated by Pedersen Zari and Hecht, through the creation of an online interactive database that highlights design interventions to support ecosystem system services [30]. Conceptual but feasible opportunities could be promoted for early piloting, and theoretical but possible opportunities earmarked for further academic and interdisciplinary investigation.…”
Section: Transitions In Maturing Marketsmentioning
confidence: 99%
“…If designers and policy makers are to effectively use ecosystem service models and concepts in urban settings, they must understand how these ecosystem services are related [ 14 , 15 ]. This is so potential synergies between ecosystem services can be leveraged, but also so that potential trade-off relationships between certain ecosystem services can be avoided or addressed [ 16 ]. To date, little research has examined relationships between ecosystem services for an urban design context (but see: [ 1 , 16 , 17 ]).…”
Section: Introductionmentioning
confidence: 99%
“…This is so potential synergies between ecosystem services can be leveraged, but also so that potential trade-off relationships between certain ecosystem services can be avoided or addressed [ 16 ]. To date, little research has examined relationships between ecosystem services for an urban design context (but see: [ 1 , 16 , 17 ]). This research seeks to address this gap in knowledge.…”
Section: Introductionmentioning
confidence: 99%